Mengembalikan Kejayaan Industri Kerajinan Cadas Silakarang di Kabupaten Gianyar melalui Penerapan Teknologi Cadas Termokromik Buatan - Karyasa, I Wayan; Astawa, I Gede Putu; Pradnyana, I Made Ardwi (Jurnal Pemberdayaan Masyarakat, 2021)
Covid-19 pandemi affects most of craft industries, including the formerly fabulous Silakarang stone’s arts and crafts located in the Gianyar Regency, Bali Province. Environmental issues regarding to river basin ecological protection along Ubud and Sukawati Districts, the mining of basaltic stones from the river banks was restricted strictly by the government. Thus, the natural stones resources for the Silakarang crafts became more difficult to afford. Hence, todays the Silakarang stone craftsmen are more and more dependent on the so-called white stone of Yogya from Java Island. Artificial stone, composing of volcanic ashes, rice husk ash silica-carbon nanocomposite, Portland cement could be the solution the problem. The addition of thermochromic natural inorganic pigment to the mixture could improve their color and performance of the artificial stones. The implementation of the thermochromic artificial stones technology to solve the stone crafts problem was conducted through community service using the participatory action and learning system approuch. As results, the artificial thermochromic stone crafts and arts products could be well accepted by costumers and it impacted to better selling of the stone crafts. The craftsmen gained better income and the Silakarang stone arts and crafts enterprises could better survive among the pandemic time.